2019
DOI: 10.1097/qai.0000000000001886
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Network Factors Associated With Racial Disparities in HIV Among Young Men Who Have Sex With Men: Results From the RADAR Cohort Study

Abstract: Background: Individual sexual risk behaviors have failed to explain the observed racial disparity in HIV acquisition. To increase understanding of potential drivers in disparities, we assessed differences across individual, network, and social determinants. Methods: Data come from RADAR (N=1015), a longitudinal cohort study of multilevel HIV-risk factors among young men who have sex with men (YMSM) aged 16–29 in Chicago. Data collection includes biological specimens; network data, including detailed informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 29 publications
5
74
1
Order By: Relevance
“…In our study, we found minor differences in mean degree by race/ethnicity, with the fewest ongoing main and casual partnerships among black and Hispanic men, respectively, and a white/black difference of nearly 3 one-time partners per year. By this measure alone, network risks were lower among black MSM, consistent with previous research (41,42). However, we found other network features that could be contributing to these disparities.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we found minor differences in mean degree by race/ethnicity, with the fewest ongoing main and casual partnerships among black and Hispanic men, respectively, and a white/black difference of nearly 3 one-time partners per year. By this measure alone, network risks were lower among black MSM, consistent with previous research (41,42). However, we found other network features that could be contributing to these disparities.…”
Section: Discussionsupporting
confidence: 91%
“…6,17 Empirical studies across multiple populations of MSM have suggested some racial differences in network degree, although the results are not consistent. 22,26,27 We found that the level of bias in degree measurements was higher for black MSM compared to white MSM, and conversely the accuracy of baseline ongoing status was highest in white-white partnerships. We had hypothesized that the groups with higher HIV incidence (black MSM) would overestimate degree less than groups with lower incidence (white MSM), which would strengthen the role of network factors in understanding disparities.…”
Section: Discussionmentioning
confidence: 77%
“…The FRP may not have strong explanatory power for racial disparities, similarly to how differences in sexual behaviors between racial groups have not fully explained disparities. 9,46 Limitations. There are several limitations to our analysis.…”
Section: Discussionmentioning
confidence: 99%